(x^2 - căn bậc hai(2))/(x^4 +(căn bậc hai(3) -căn bậc hai(2))*x^2 - căn bậc hai(6))
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Những câu hỏi liên quan
D
0
\(\frac{x^2-\sqrt{2}}{x^4+\left(\sqrt{3}-\sqrt{2}\right)x^2-\sqrt{6}}=\frac{x^2-\sqrt{2}}{x^4+\sqrt{3}x^2-\sqrt{2}x^2-\sqrt{6}}\)
\(=\frac{x^2-\sqrt{2}}{x^2\left(x^2+\sqrt{3}\right)-\sqrt{2}\left(x^2+\sqrt{3}\right)}=\frac{x^2-\sqrt{2}}{\left(x^2-\sqrt{2}\right)\left(x^2+\sqrt{3}\right)}=\frac{1}{x^2+\sqrt{3}}\)